Weighted Ensemble Classifier for Plant Leaf Identification - R. Putri Ayu Pramesti; Yeni Herdiyeni; Anto Satriyo Nugroho (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Plant leaf identification using image can be constructed by ensemble classifier. Ensemble classifier executes classification of various features independently. This experiment utilized texture feature and geometry feature of plant leaf to find out which features are more powerful. Each classifier trained by specific feature produced different accuracy rate. To integrate ensemble classifier the results of the classification were weighted, so as the score obtained from better features contributed greater to the final results. Weighted classification results were combined to get the final result. The proposed method was evaluated using dataset comprises of 156 variety of plants with 4559 images. Weighting and combining classifier used in this study were Weighted Majority Vote (WMV) and Naïve Bayes Combination. Both of those method result showed better accuracy than using single classifier. The average accuracy of single classifier was 61.2% for geometry classifier and 70.3% for texture classifier, while WMV method was 77.8% and Naïve Bayes Combination was 94.6%. The calculation of classifier’s weight by using WMV method produces a weight value of 0.54 for texture feature classifier and 0.46 for geometry feature classifier.